2018
DOI: 10.1128/aac.02151-17
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of the LolCDE ABC Transporter Essential for Lipoprotein Trafficking in Gram-Negative Bacteria

Abstract: The outer membrane is an essential structural component of Gram-negative bacteria that is composed of lipoproteins, lipopolysaccharides, phospholipids, and integral β-barrel membrane proteins. A dedicated machinery, called the Lol system, ensures proper trafficking of lipoproteins from the inner to the outer membrane. The LolCDE ABC transporter is the inner membrane component, which is essential for bacterial viability. Here, we report a novel pyrrolopyrimidinedione compound, G0507, which was identified in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 46 publications
1
72
1
Order By: Relevance
“…In MacB, the stalk structure is intimately connected with mechanotransmission, suggesting that G0507 and C2 exert their effects by interfering with analogous movements necessary for coupling LolCDE's cytoplasmic ATPase activity with the lipoprotein transfer reaction. Consistent with this "mechanotransmission uncoupling" as a hypothesis for the action of these inhibitors, G0507 is known to stimulate ATPase activity of LolCDE while inhibiting the release of lipoproteins from the inner membrane (19). Because C2 also inhibits lipoprotein release, we tested its effect on LolCDE ATPase activity and found that, like G0507, C2 causes an increase in the rate of hydrolysis (SI Appendix, Fig.…”
Section: Inhibition Of Lolcde By Compound 2 Proceeds By Mechanotransmmentioning
confidence: 57%
See 3 more Smart Citations
“…In MacB, the stalk structure is intimately connected with mechanotransmission, suggesting that G0507 and C2 exert their effects by interfering with analogous movements necessary for coupling LolCDE's cytoplasmic ATPase activity with the lipoprotein transfer reaction. Consistent with this "mechanotransmission uncoupling" as a hypothesis for the action of these inhibitors, G0507 is known to stimulate ATPase activity of LolCDE while inhibiting the release of lipoproteins from the inner membrane (19). Because C2 also inhibits lipoprotein release, we tested its effect on LolCDE ATPase activity and found that, like G0507, C2 causes an increase in the rate of hydrolysis (SI Appendix, Fig.…”
Section: Inhibition Of Lolcde By Compound 2 Proceeds By Mechanotransmmentioning
confidence: 57%
“…LolA has been docked according to LolA-LolC crystallographic data (6F3Z). Positions at which mutations confer resistance to both compound 2 (21) and G0507 (19) inhibitors are shown mapped to the ATP-bound state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OM is also essential for bacterial growth and therefore is a great molecular target for novel antibiotic intervention. To this end, small molecule inhibitors against the Lol (108,109) and MsbA/Lpt pathways (105,110) have already been identified. Continued efforts in deciphering PL-trafficking processes will ultimately yield new targets that can be exploited for combating Gram-negative bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%